Host Specificity of the Dickeya Bacteriophage PP35 Is Directed by a Tail Spike Interaction With Bacterial O-Antigen, Enabling the Infection of Alternative Non-pathogenic Bacterial Host - Kabanova, Anastasia P.; Shneider, Mikhail M.; Korzhenkov, Aleksei A.; Bugaeva, Eugenia N.; Miroshnikov, Kirill K.; Zdorovenko, Evelina L.; Kulikov, Eugene E.; Toschakov, Stepan V.; Ignatov, Alexander N.; Knirel, Yuriy A.; Miroshnikov, Konstantin A. (Frontiers in Microbiology, 2019)
Dickeya solani, a recently emerged virulent bacterial potato pathogen, is a major threat to world agriculture. Because of the growing limitations in antibiotic use, the alternative strategies of bacteriosis control are considered, including the application of bacteriophages. Myoviridae bacteriophages recently re-ranked as a separate family Ackermannviridae are the attractive candidates for this purpose, and phage PP35 described in this paper is a good example of such potential phage. High specificity of PP35 is explained by the presence of the tail spike protein PP35 gp156 possessing enzymatic activity of depolymerization of the O-polysaccharide (OPS) of D. solani. The outer polysaccharide structure, →2)-β-D-6-deoxy-D-altrose-(1→, is unique among soft-rot Pectobacteriaceae, however it may be also present in non-virulent environmental Enterobacteriaceae. The phage tail spike depolymerase degrades the shielding polysaccharide, and launches the cell infection process. Thus, non-pathogenic commensal bacteria may maintain the population of the phage in soil environment. Also, such bacteria may serve as non-pathogenic host for the industrial production of phages.